2017
DOI: 10.3390/ijms18122744
|View full text |Cite|
|
Sign up to set email alerts
|

Tussilagone Inhibits the Inflammatory Response and Improves Survival in CLP-Induced Septic Mice

Abstract: Tussilagone, extracted from Tussilago farfara is an oriental medicine used for asthma and bronchitis. We investigated its mechanism of action, its inhibitory effects on lipopolysaccharide-induced inflammation in macrophages, and its impact on viability in a cecal ligation and puncture (CLP)-induced mouse model of sepsis. Tussilagone suppressed the expression of the inflammatory mediators, nitric oxide and prostaglandin E2, and the inflammatory cytokines, tumor necrosis factor-alpha (TNF-α) and high-mobility gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…Comparatively, most previous studies have suggested that TUS suppresses the activation of NF-kB pathway, while the modulated targets vary. Cheon et al (2018), Choi et al (2018), Hwang et al (2018), Kim et al (2017b), Lee et al (2016) and Lim et al (2008) all have reported that TUS blocks NF-kB pathway in exogenous-agent-induced colitis mice, airway epithelial cells, focal cerebral ischemia rats, septic mice, skin inflammation mice, and BV-2 microglial cells by attenuating the nuclear translocation of p65 subunit and the phosphorylation and (or) degradation of IkBa. Among them, Choi et al (2018) have also observed the alleviation of phosphorylated IKK complex.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Comparatively, most previous studies have suggested that TUS suppresses the activation of NF-kB pathway, while the modulated targets vary. Cheon et al (2018), Choi et al (2018), Hwang et al (2018), Kim et al (2017b), Lee et al (2016) and Lim et al (2008) all have reported that TUS blocks NF-kB pathway in exogenous-agent-induced colitis mice, airway epithelial cells, focal cerebral ischemia rats, septic mice, skin inflammation mice, and BV-2 microglial cells by attenuating the nuclear translocation of p65 subunit and the phosphorylation and (or) degradation of IkBa. Among them, Choi et al (2018) have also observed the alleviation of phosphorylated IKK complex.…”
Section: Discussionmentioning
confidence: 97%
“…TUS, the main component of T. farfara, was described to have anti-platelet-aggregation and cardiovascular-respiratory stimulating effects in previous studies (Hwang et al, 1987;Li and Wang, 1988). In recent years, several studies have proven beneficial in the treatment of diseases such as diabetic obesity (Park et al, 2008), cancers , and various inflammatory diseases (Lee et al, 2016;Kim et al, 2017b;Cheon et al, 2018;Choi et al, 2018;Hwang et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations